Online Quiz as a Form of Career Guidance - Kharchenko, Yuliia; Babenko, Olena; Danylchenko, Olena (Pedagogical Discourse, 2021)
The article is devoted to the issue of organizing career guidance activities at universities. The results of external independent testing for the period 2016–2020 were analyzed. It was found that over the last five years the number of graduates who registered for testing in chemistry and graduates who reached the passing score significantly decreased. This negative trend leads to decreasing number of future applicants for chemical specialties, including pedagogical ones. This fact leads to an aggravation of the higher educational institutions struggle for graduates. The authors emphasize the need to search for new forms of career guidance, including because of the quarantine restrictions caused by the COVID-19 pandemic. The authors consider the possibility of using online quizzes for career guidance providing. So, the Open Day of the Department of Chemistry and Methods of Teaching Chemistry of A.S. Makarenko Sumy State Pedagogical University was held and an online quiz in chemistry was developed. The online format of the event made it possible to significantly expand the geography of the participants. This made it possible to obtain data from the participants in order to subsequently inform them about the events that will be conducted by the department, as well as to keep in touch with potential applicants. All participants of the quiz were asked to answer the questionnaire in order to find out their opinion about the event and find out if they were interested in our university and our department after participating in the quiz. The results showed that participation in the event aroused interest of students in the university and the department. The most convenient ways of feedback from students were also found out. The need to intensify cooperation with teachers was noted. In general, the results of the analysis of the responses received allow us to draw a conclusion about the potential effectiveness of such online events for career guidance.